The rural energy project = (The World Bank in Vietnam (WB), 2003)
The Rural Energy Project for Vietnam aims to expand rural access to electricity in communes located in 32 provinces through grid extension, where economically justified, to improve welfare, enhance income-earning capacity and help alleviate poverty; 2) to define and establish institutional mechanisms and strategy for rural electrification; and 3) promote the application of renewable energy sources in areas inaccessible to the national grid and to supplement grid power supply. The first three components include the construction of transmission lines, substations, and consumer meters, etc. in northern, southern, and central regions. The fourth component provides technical assistance and capacity building for project management and coordination including staff development and training; improves management systems in the state power agency; prepares a pilot cooperative for investment, management, and operation of rural power distribution at the commune level; and lastly helps fund feasibility studies for a system and energy efficiency improvement program